Synthesis, isomerization, and DFT studies of five-membered heterocyclic ketoximes. Issue 11 (November 2021) - Su, Biyun; Han, Qiaoqiao; Li, Xiaoteng; Hou, Yifan; Wu, Jindi; Wang, Li; Ding, Liqin
A homologous series of five-membered heterocyclic ketoximes is synthesized by condensation reactions of 2-acetylpyrrole, 2-acetylthiophene, and 2-acetylfuran with hydroxylamine hydrochloride. These compounds were fully characterized by X-ray single-crystal diffraction, elemental analysis, 1 H NMR, IR, UV-Vis, and fluorescence spectra. Interesting isomerization phenomena are observed for these heterocyclic ketoximes by different characterization methods. By means of 1 H NMR and X-ray single-crystal diffraction, it was found that 2-acetylpyrrole oxime (1 ) exists as the Z -type geometric isomer, 2-acetylfuran oxime (3 ) exists as the E -isomer, while 2-acetylthiophene oxime (2 ) is identified as a mixture of Z- and E -isomers. To study the above phenomena further, quantum chemical calculations of total energy, dipole moment, E HOMO, E LUMO, and other parameters of each heterocyclic ketoxime were carried out by Density functional theory (DFT). The theoretical calculations were in good accordance with the experimental spectroscopic results.